Measuring Hybrid e-Logistics Service Quality from B2C e-Commerce - Virantau, Gilbert Nathaniel; Rahayu, Siti; Trisnawati, Juliani Dyah (Journal of Entrepreneurship & Business, 2025)
Purpose: This study aims to test and analyze two hybrid models of logistics service quality (LSQ) and their influence on satisfaction, loyalty, and purchase intent in the future. The context of this research is business-to-consumer (B2C) e-commerce with a case study on Tokopedia. This study integrates the traditional LSQ model that adds 3 dimensions, namely order availability, order returns, and quality assurance consisting of the quality of personnel contacts, handling of order non-conformities, and the return process. Method: The survey was conducted by distributing a questionnaire through a google form. Respondents were selected based on predetermined criteria, and data were analyzed using structural equation modelling to examine the relationship between research variables. Result: The results of the study showed that 6 hypotheses were supported and 4 hypotheses were not supported. Order accuracy, order availability, ordering procedures, and quality assurance affect customer satisfaction. Customer satisfaction affects loyalty, and loyalty affects future purchase intention. Hypotheses 1, 2 and 5, namely the influence of timeline, order conditions and information quality on customer satisfaction are not supported. Hypothesis 9 is also unsupported, which suggests that customer satisfaction has no significant effect on future purchase intention.